Creation myths of the world an encyclopedia - Leeming, David Adams 1937- (Gale virtual reference library, 2010)
Provides a comprehensive resource on creation myths from around the world, their narratives, themes, motifs, similarities, and differences-and what they reveal about their cultures of origin.